Transition metal salphen DNA complexes as biosensor application for detecting various mosquito viruses - Monajjemi, Majid; Mollaamin, Fatemeh (Emerald, 2023)
Purpose Piperidine side chain-functionalized N, N′-bissalicylidene phenylene di amine di-anion (salphen) consisting of salphen-Zn and salphen-Cu are able to intercalate with nucleic base stacking of DNA and can be applied as an optical DNA hybridization detector. Attaching DNA and salphen to glass surfaces has been done via coating the surface with the silane coupling agents containing 3-aminopropyltriethoxysilane that was synthesized for acting as a high-affinity RNA carrier matrix. The Schiff base salphen-zinc (II) and salphen-Cu (II) complexes-labelled probe to target nucleic acid renders a colour change of the DNA biosensor to a green and red background colour for zinc and copper, respectively. This study aims to indicate that the DNA biosensor data with high efficiency is used for detection of dengue virus serotypes 2 (DENV-2) and Chikungunya virus (CHIKV) concentration via salphen-Zn (II) and salphen-Cu (II), respectively, in human samples. Design/methodology/approach 1H-NMR and 13C-NMR have been used via PerkinElmer LAMBDA 35 instrument. The authors also used a double beam spectrophotometer with (CH3)4Si (TMS) as reference and dimethyl sulfoxide as solvent reference in pH = 7.0. Various DNA concentrations have been used for UV spectrophotometry at 300 nm and 400 nm for zinc and copper complexes, respectively. BRUKER mass spectra with DIONEX Ultimate 3000 LC model were used for all measurements. Mettler Teledo model (DSC882e) of differential scanning calorimeter (DSC) was used for measure the melting temperature of metal zinc and copper complexes. The morphology of the silica Nano spheres (SiNs) were scanned by FESEM with Model JSM-6700F from Japan. Findings The Cu (II) and Zn (II)-salphen-viruses DNA system for CHIKV and DENV-2, respectively, in different concentration have been investigated via various spectroscopies (Figure 3). CHIKV and DENV-2 DNA were selected from human saliva and urine samples as models for conformations of human G4-DNA. By increasing the amounts of DNAs, and G4, the UV–Vis bands of located above 300 nm, experienced a hypochromic effect. The Cu2+ complex exhibits selectivity towards the G4, and there is a similar affinity for Zn2+ complex binds to the G4. These results collectively suggest that the Cu2+ complex is stronger than the Zn2+ complex. The authors have found copper (II) and zinc (II) compounds and nucleic acid-complexes are strongly fluorescent molecules in the low energy range, from the visible to the near-infrared. Since the fluorescent emission of Zn (II) and Cu (II) complexes are enhanced by the binding to nucleic acids upon visible light exposure when bound to DNA. These complexes are important as selective fluorescent probes for nucleic acids and to highlight their potential application. UV–vis spectroscopy is an accurate for finding the extent of ligand interaction with DNA and metallic complexes–DNA binding. Generally, the binding of intercalative compounds to DNA can be characterized through absorption spectral titrations, where lowering in absorbance (hypochromism) and shift to longer wavelengths (red shift) were observed in this work. Originality/value The serum samples have been provided as citrate and collected in tubes after blood is allowed to clot. Then, it has been separated by centrifugation, and the authors have kept serum refrigerated at 4°C or frozen at –20°C. It is notable; specimens have been confirmed by Centres for Disease Control (CDC)-Dengue Branch previously. For the work, these samples have been frozen previously, and the diagnostic practiced tests at the CDC-Dengue Branch have been validated in serum and plasma. Therefore, plasma separated in lavender or heparins are suitable and acceptable for serology testing.
Keywords: 3. Good health